PENDAMPINGAN PENYUSUNAN MODEL PROSES BISNIS DENGAN PROTOKOL KESEHATAN NEW NORMAL DI DESA WISATA KALISUCI, GUNUNGKIDUL - Galih Jati Mumpuni; Ilsa Haruti Suryandari (Universitas Sanata Dharma, 2021)
The Covid-19 pandemic has resulted in restrictions on activities in various fields, which have an impact on the decline in the level of the economy. The tourism sector is one of the sectors experiencing the biggest losses due to the current pandemic. Therefore, an adaptation step is needed to ensure the operation of tourism activities, which is the additional of a health protocol to the business process of tourism activities. Kalisuci Tourism Village is one of the tourism villages that implements health protocols in its business processes. However, the implementation of this protocol has not been documented therefor it cannot be evaluated periodically. This community service activity aims to assist tourism village managers in analyzing and documenting business processes with health protocols. This service is expected to help Kalisuci Tourism Village to have business process documentation as a guide to implement standards services for tourists. The methods used in this activity were observation, analysis and evaluation, as well as mentoring services. The results of this activity consist of 3 business process documentation for each business unit in Kalisuci Tourism Village.